Ethnographies of Waiting Doubt, Hope and Uncertainty (Edition 1) - Bandak, Andreas; Janeja, Manpreet K. (Routledge, 2020)
We all wait - in traffic jams, passport offices, school meal queues, for better weather, an end to fighting, peace. Time spent waiting produces hope, boredom, anxiety, doubt, or uncertainty. Ethnographies of Waiting explores the social phenomenon of waiting and its centrality in human society. Using waiting as a central analytical category, the book investigates how waiting is negotiated in myriad ways. Examining the politics and poetics of waiting, Ethnographies of Waiting offers fresh perspectives on waiting as the uncertain interplay between doubting and hoping, and asks "When is time worth the wait?" Waiting thus conceived is intrinsic to the ethnographic method at the heart of the anthropological enterprise. Featuring detailed ethnographies from Japan, Georgia, England, Ghana, Norway, Russia and the United States, a Foreword by Craig Jeffrey and an Afterword by Ghassan Hage, this is a vital contribution to the field of anthropology of time and essential reading for students and scholars in anthropology, sociology and philosophy.